Presence of epidermal growth factor receptor as an indicator of poor prognosis in patients with breast cancer. - Sainsbury, J R (1985)
Epidermal growth factor receptors are present in some breast cancers in man, and there is an inverse relation to oestrogen receptor state. We assessed the presence of epidermal growth factor receptors as a single prognostic indicator in a series of breast tumours by comparing this with the Bloom and Richardson scores for these tumours. One hundred and eight ductal tumours were examined for epidermal growth factor receptors by radioligand binding. There was a significant (p less than 0.01) correlation between the presence of the growth factor receptor and poor prognosis as assessed by the Bloom and Richardson score, suggesting that epidermal growth factor receptor state could be a useful prognostic marker. Epidermal growth factor receptor state was not significantly correlated with the lymph node state but showed a tendency to be associated with large tumours.